Message from the Editorial - Nantikanjana, Ratchaneekorn (FOYER: The Journal of Humanities, Social Sciences, and Education, 2019)
This Liberal Arts Journal, the Faculty of Liberal Arts, Mahidol University is publication of Vol 2, No 2, July – December 2019. There are 4 articles which have been selected from experts and containing diverse contents– teaching and learning, culture, politics, and government. They are quality articles providing the benefits for educators, researchers, and students.